ANALISIS FINANSIAL USAHA TANI TANAMAN HIAS RAPHIS EXCELSA (STUDI KASUS KELOMPOK TANI LABUAI, JALAN HUSADA,KECAMATAN BUKIT RAYA, KOTA PEKANBARU) - Rahmat Sholihin; Suardi Tarumun; Didi Muwardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Raphis excelsa, also called Palemwaregu now become popular as ornamental plants. This kind of palms are cultivated and exported to overseas. The purpose of this reserch is to analyze the financial feasibility of ornamental plants Raphis excelsa farming. The research is done in Labuai, District Bukit Raya, Pekanbaru City. Farmers Group in Labuai received funding aid from the Food and Horticulture office of Pekanbaru City. The land area is about ​​0.5 ha.Financial analysis criteria used in this reserch are Net Present Value (NPV), Net Benefit Cos Ratio (Net B/C), Internal Rate of Return (IRR) and sensitivity analysis. The research results showed that Raphis excelsa farming hasperformed well and its financial criteria of NPV, Net BC ratio and IRR has met the standard investment criteria. The sensitivity analiysis showed that when input prices increase by 50% and output prices decrease 20% the results of sensitivity analysis still meet the standard investment criteria. Keyword: Raphis excelsa, Investment criteria, Sensitivity analysis.